Modelamiento de la cinética de secado de Bixa Orellana L. (achiote) por dos modelos matemáticos de Bet y Gab - Quinteros Navarro, Jerónimo (2024)
In the present investigation, the drying kinetics of Bixa orellana L (achiote) were evaluated using two mathematical models, the B.E.T model (Brunauer, Emmet and Teller) and the G.A.B model (Guggenheim, Anderson and De Boer) in a dryer. of trays by forced convection at temperatures of 50 °C, 60 °C and 70 °C, maintaining constant the thickness of the bed to be dried, which is 5 mm and the air speed, which is 5 m/s. During the drying process, the critical humidities were determined, which decreased from 2.594 kg/kg s.s to 2.360kg/kg s.s. This same behavior is also presented by the equilibrium humidity, which has 0.127 kg/kg s.s. It decreases to 0.097 kg/kg s.s., showing a dependence on the drying temperature, likewise the drying speed increased from 1,564 kg/h m2 at a temperature of 50 °C to 2,181 kg/h m2 for the temperature of 70 °C indicating a greater mass transfer due to direct influence of the temperature, The Activation Energy and Effective Diffusivity are calculated from the Arrhenius equation where both values are increased by the effect of temperature and the composition of the raw material, these values are from 6,588 J/mol K to 9,554 J/ mol K from 50 °C to 70 °C respectively for the activation energy and from 0.110 m2/s to 0.182 m2/s for the effective diffusivity also at temperatures from 50 °C to 70 °C. The mathematical models of B.E.T and G.A.B have been graphed and are shown in figures 20, 21 and 22 where the G.A.B model (Guggenheim, Anderson and De Boer) better represents the drying kinetics process.